Occurrence and molecular phylogeny of Fasciola species in camels of southwestern Iraq - Isra’a M. Essa; Ghazi Y. Azzal (Veterinary World)
Background and Aim: Fasciola spp. are important trematodes of public health concern in various animals, including camels. This study aimed to determine the occurrence of liver flukes in camels, to determine the molecular confirmation of Fasciola, and to perform phylogenetic analysis of study isolates to identify the species of Fasciola.